Development Of Multicultural Islamic Education At The Nurulhuda Islamic Boarding - Saifurrahman, Awzar Fannany; Najah, Zughrofiyatun (Al-Ishlah: Jurnal Pendidikan Islam, 2024)
Multicultural religious education has been widely studied and studied with different scientific views, differences in the diversity of origins of the population, teachers and students at the Nurulhuda Padangangan Islamic boarding school in Sumenep. According to researchers, it is important to know the development of multicultural Islamic education in the Nurulhuda Padangangan Islamic boarding school environment in Sumenep. Therefore, researchers examine this research by knowing the development of multicultural Islamic education at the Nurulhuda Padangangan Islamic boarding school in Sumenep. Nurulhuda Islamic boarding school is one of the Islamic educational institutions that was founded to create an atmosphere of peace and provide more knowledge, thoughts, knowledge and experience for Muslims. And the Nurulhuda Islamic boarding school. Multicultural education is a necessity for the Indonesian people in facing global challenges in the future where the demands on the Islamic religion are increasing, getting bigger and more complex.